A Study of Critical Success Factor for Green Technology Implementation - Nor Harlina, Abd Hamid (2011)
There are several issues keep in talking and always be an issues in any conference today that come to attention than others. One of these issues is Green Technology. For the purpose of this research, it only will be focused on the implementation of green technology. This research explores the factors that influence the green technology implementation. More specifically, there are four causes that lead to the green technology implementation which are attitude, government policies, cost effectiveness and free hazardous environment. There is a sample of 103 was chosen as the respondents and questionnaires regarding their intention on this issue was asked. From the correlation and regression analysis done, it was concluded that there is a positive relationship between the critical success factors of attitude, policy, cost effectiveness and free hazardous environment on green technology implementation within three industries in Malaysia; retailing, manufacturing and services. In general, it can be concluded that industrial companies should be aware of the importance and impact of green technology not only to the companies themselves, but also to the communities as a in order to preserve our earth.